Kidscreen : quality of life in children and adolescents - Gaspar, Tânia, 1977- (2012)
The KIDSCREEN is a European cross-cultural and standardized instrument that assesses ten quality of life dimensions in children, adolescents and their parents. The get validity evidences to support general inferences on quality-of-life measures obtained by Portuguese version of KIDSCREEN-52 for children and adolescents, in the context of a survey research. The present study focuses only in the KIDSCREEN children and adolescents versions. A sample of 3195 children and adolescents from 5th grade (48,8%) and 7th grade (51,2%), mean age 11,8; SD 1,46; 49,2 % boys, were inquired. KIDSCREEN instrument showed a good internal consistency for most of the 10 subscales, with a lower value for a self-perception (á= 0, 60) and the highest for financial resources (á= 0, 88). In order to test the theoretical model fit index an exploratory factor analysis and a confirmatory factor analysis were used. The RMSEA value was 0, 06 can be consider a good fit index. The CFI value is 0, 97 and NNFI is 0,97 reflecting both an excellent fit index.KIDSCREEN-52 questionnaire is a reliable instrument to estimate the perception of quality of life in children and adolescents. (Tânia Gaspar... [et al.])